Novel apatite KLaSr3(PO4)3F:Eu2+ phosphors: synthesis, structure, and luminescence properties. Issue 22 (18th October 2016) - Guo, Qingfeng; Zhao, Chenglong; Liao, Libing; Lis, Stefan; Liu, Haikun; Mei, Lefu
Abstract: Abstract : A series of novel KLaSr3− x (PO4 )3 F: x Eu 2+ phosphors were synthesized for the first time. The crystal structure, photoluminescence properties, concentration quenching, decay analysis, and the temperature dependent luminescence properties were investigated in detail. The unit cell parameters for KLaSr3 (PO4 )3 F were estimated to be a = 9.8997 Å, c = 7.4075 Å, and V = 628.7 Å 3 . The photoluminescence excitation spectrum of KLaSr3 (PO4 )3 F:Eu 2+ shows a broad band from 225 nm to 450 nm with a maximum at about 320 nm. KLaSr3− x (PO4 )3 F: x Eu 2+ phosphors exhibit a wide emission band ranging from 425 to 550 nm. KLaSr3 (PO4 )3 F:Eu 2+ phosphors exhibit good thermal stability up to 423 K. KLaSr3 (PO4 )3 F:Eu 2+ was fabricated with commercial green (Ba, Sr)SiO4 :Eu 2+ and red CaAlSiN3 :Eu 2+ phosphors to obtain a white-light-emitting diode. All the results demonstrate that KLaSr3 (PO4 )3 F:Eu 2+ are promising blue phosphors for white-light ultraviolet light-emitting diode applications.